Public health risk analysis due to consuming Tilapia (Oreochromis niloticus) containing heavy metals in Bakan village, Lolayan district, Bolaang Mongondow regency - Maddusa, Sri Seprianto; Asrifuddin, Afnal; Mantjoro, Eva Mariane (International Journal Of Community Medicine And Public Health, 2022)
Background: Gold mining activities, both legal or illegal, as well as public activities that live around Bakan River influenced the quality of water. These activities produce waste that contains heavy metals from gold production and derivative impacts of these activities. The waste then flows into the water and pollute the water and biota. People that use the water feel the impact like health problems. Tilapia (Oreochromis niloticus) is one of the fish in Bakan river that often consumed by people. Consuming fish that exposed to heavy metals in certain concentration is very dangerous for public health. A public health risk analysis is needed to estimate the magnitude of the impact. The research location is in the river on Bakan village, Lolayan district, Bolaang Mongondow regency. The aim of the study is to determine the levels of heavy metals Arsenic (As), Cadmium (Cd), Chromium (Cr), Mercury (Hg) and Lead (Pb) in Tilapia (Oreochromis niloticus)’s organs. Methods: The type of this study is observational with Environmental Health Risk Assessment (EHRA) approach, where the number of respondents is 100 people. Results: The results showed that the concentration of Cd (0.01<0.10), Cr (<0.1) and Pb (0.1<0.20) in fish is still below quality standard based on BPOM No. 23 of 2017. Health risk estimates obtained RQ>1 for metal As and Hg. Conclusions: This study has proven that consuming Tilapia is not safe for health.